Pengaruh Kecepatan Pengadukan pada Proses Stircasting terhadap Sifat Mekanik pada Paduan Aluminium - Jauhari, Mochamad Helmi; Darmadi, Djarot B; Widodo, Teguh Dwi (Jurnal Rekayasa Mesin, 2021)
The composite material is a material composed of a mixture or combination of two or more of the major elements that macro differ in shape and material composition that basically can not be separated. In this research, the aluminum used was the outcome of production cesspool with the addition of volcanic dust from Mount Kelud by 2% as reinforcement. The stir casting process is the casting process by adding a material (powder form) in pure metal (aluminum), which has been melted and then stirring constantly. After that, the composite materials (the volcanic dust from Mount Kelud) were mixed slowly into the stirred liquid material. In this research, the variations of stirring speed were 0,200,300,400,500Â  and 600 rpm. The stirring each time for 4 minutes. In this study, the stirring speed in the casting process was 0, 200, 300, 400, 500, and 600 rpm. Tensile test, Impact test, and microstructure observations were carried out on the casting results. From these tests, the highest modulus of elasticity and impact value was obtained at the 600rpm stirring process. It may due to globular grains are more evenly distributed. And the result of metallographic testing was stirring speed could affect the amount and density of composite grain structure. The faster the stirring, the grain structure was getting smaller and close.